2018
DOI: 10.1128/jvi.00858-18
|View full text |Cite
|
Sign up to set email alerts
|

Protein Mismatches Caused by Reassortment Influence Functions of the Reovirus Capsid

Abstract: Following attachment to host receptors via σ1, reovirus particles are endocytosed and disassembled to generate infectious subvirion particles (ISVPs). ISVPs undergo conformational changes to form ISVP*, releasing σ1 and membrane-targeting peptides from the viral μ1 protein. ISVP* formation is required for delivery of the viral core into the cytoplasm for replication. We characterized the properties of T3D/T3DS1, an S1 gene monoreassortant between two laboratory isolates of prototype reovirus strain T3D: T3D an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 92 publications
(135 reference statements)
5
11
0
Order By: Relevance
“…T3D/T1L L3S2 and T3D ISVPs were heated to 40°C and loss of infectivity was measured by plaque assay. Consistent with previous work (20), at 40°C, most of the T3D ISVPs did not convert to ISVP* and the change in titer was minimal (Fig 2C). However, heating T3D/T1L L3S2 ISVPs to 40°C resulted in ISVP* conversion and a significant loss in infectivity (Fig 2C).…”
Section: Isvp To Isvp* Conversion Efficiency Of T3d Is Altered By the T1l Core Proteins λ1supporting
confidence: 92%
See 1 more Smart Citation
“…T3D/T1L L3S2 and T3D ISVPs were heated to 40°C and loss of infectivity was measured by plaque assay. Consistent with previous work (20), at 40°C, most of the T3D ISVPs did not convert to ISVP* and the change in titer was minimal (Fig 2C). However, heating T3D/T1L L3S2 ISVPs to 40°C resulted in ISVP* conversion and a significant loss in infectivity (Fig 2C).…”
Section: Isvp To Isvp* Conversion Efficiency Of T3d Is Altered By the T1l Core Proteins λ1supporting
confidence: 92%
“…and σ2. Single gene reassortants between prototype reovirus strains T1L and T3D, which contain mismatches between outer capsid proteins, display altered capsid stability and efficiency of disassembly intermediate formation (19)(20)(21). To determine whether the core proteins λ1 and σ2 play a role in ISVP-to-ISVP* conversion efficiency, we characterized the properties of T3D/T1L L3S2.…”
Section: Isvp To Isvp* Conversion Efficiency Of T3d Is Altered By the T1l Core Proteins λ1mentioning
confidence: 99%
“…We observed that segments S1 and M2 are genetically linked, which indicate that the structure and interaction of their encoded proteins are vital for virus fitness. For MRV, an in vitro forced reassortment event has been reported to alter virus infectivity and replication efficiency due to λ2 and σ1 protein mismatch [52].…”
Section: Discussionmentioning
confidence: 99%
“…Work using reassortant viruses engineered in a laboratory indicates that σ1 and λ2, and their interactions with other outer capsid proteins, can play additional unexpected roles during entry. A reassortant virus (T3D F /T3D C S1) which contains nine gene segments from the laboratory strain T3D F and the S1 gene segment (encoding σ1) from the laboratory variant T3D C demonstrated lower stability and more efficient ISVP-to-ISVP* transition in comparison to T3D F [ 60 ]. Thus, properties of σ1 can affect the stability of ISVPs.…”
Section: Role For Other Reovirus Capsid Proteins In Controlling Comentioning
confidence: 99%